Autonomous soft open point control for active distribution network voltage level management - (:unkn) unknown (IEEE, 2019)
With rapid development towards sustainable smart grids, the future electricity distribution networks should be able to host more and more distributed generation (DG) and enable also higher demand peaks e.g., due to charging of electric vehicles (EVs). Soft Open Point (SOP) is one potential enabling solution, which could provide multiple functionalities for future active network management (ANM) and improve resiliency and flexibility of future electricity distribution networks. The focus in this paper is to design a new control method for SOP inverters in back-to-back (B2B) configuration. This paper proposes an outer autonomous reactive power controller for active voltage level management in an example medium-voltage (MV) distribution network. The developed new SOP control methods are validated with Matlab based simulation results. Results show that developed autonomous SOP control is an effective option for active voltage management in future MV networks.
Keywords: smart grid; soft open point (SOP); Volt/VAr control; droop control; fi=Sähkötekniikka|en=Electrical Engineering|